Կարապետ վարդապետ Տէր-Մկրտչեանի «Գէորգեան Ճեմարանում իմ ապրած օրերը» յուշերի առիթով - Խմբ.՝ Առաքել Առաքելյան (1944-1948); Լևոն Կիսիբեկյան (1948-1950); Աշոտ Աբրահամյան (1950-1955); Առաքել Առաքելյան (1955-1956); Արթուն Հատիտյան (1956-1982); Պարգեւ Շահբազյան (1983-1984); Երվանդ Մելքոնյան (1985-1993); Տ. Ասողիկ եպս. Արիստակեսյան (1994-1996); Տ. Բագրատ աբղ. Գալստյան (1996-1998); Մարիամ Վարդանյան (պաշտոնակատար) (1998-1999); Տ. Արշակ աբղ. Խաչատրյան (պաշտոնակատար) (1999); Անդրանիկ Զեյթունյան (2000-2001); et al. (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В архиве Ерванда Тер-Минасяна, Матенадаран им. Святого Месропа Маштоца, найдена рукопись Епископа Карапета Тер-Мкртчяна «Проведенные мною годы в семинарии Геворкян», которая издается впервые в своем полном содержании и где описаны его воспоминания начиная с первых дней поступления. В оспоминаниях автор рассказывает о случаях, связанных с ним и его друзьями, откуда мы черпаем богатую информацию о проведенных им годах, руководстве семинарии и царящей в ней обстановке. Bishop Karapet Der Mkrtchian’s document under the heading "My Days Spent at Gevorkian Seminary," which was discovered in Yervand Der-Minassian’s archive in the Matenadaran of St. Mesrop Mashdots is being published in its entirety for the first time, where the author’s memoires are presented starting from his first day at the seminary. In his memoires the author recounts the events pertaining to his friends and himself, from which we find a wealth of information regarding the faculty and the situation at the seminary.
Keywords: Biography; Auxiliary Sciences of History; Christianity; History of the Armenian Church